Peran Koneksi Politik dalam Memoderasi Environmental Social Governance Disclosure terhadap Agresivitas Pajak - Muhammad Rizal Afandi; Suwandi Suwandi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose study aims to analize the effect of the environmental social governance & tax agresivity with Role political connection as moderation variable. In this study the theory used as the basis for this test is Legistimachy theory & Political Cost Hypotesis theory, This study aims to examine the environmental, social and governance aspects of tax aggressiveness and to examine whether political connections can moderate environmental social governance on tax aggressiveness in manufacturing, mining, & agro companies listed on the Indonesia Stock Exchange (IDX).. Sample measurements in this research were using quantitative techniques. The objects used as samples in this test were 60 companies The type of data used as the research object is documentary, namely financial reports of companies by selecting the time period 2021 to 2023 respectively. This research uses outer model, inner model & hypothesis testing. The results show that each dimension of the environment social and governance does not have a direct effect on tax aggressiveness with a significance value of p value above 0.05 and t statistic shows a coefficient below 1.966. However, the indirect effect shows that political connections can act as a negative moderator of the relationship between the environment and tax aggressiveness with a significance value of p value 0.020 and t statistic 2.330. In addition, political connections can also act as a positive moderator of the relationship between governance and tax aggressiveness with a significance value of p value 0.004 and t statistic 2.906. However, political connections cannot moderate the relationship between the social environment and tax aggressiveness with a significance value of p value e 0.081 and t statistic 1.745.